Glutathione and Oxidized Low-Density Lipoprotein as Biomarkers of Oxidative Stress in Essential Hypertension - Sahito, Falak Sehar; Imtiaz, Fauzia; Qamar, Ambreen; Bhatty, Shaheen; Waseem, Hira Fatima (Journal of Liaquat University of Medical & Health Sciences, 2023)
OBJECTIVE: This study aimed to compare the serum levels of Glutathione and Oxidized Low-Density Lipoprotein in early hypertensive and normotensive subjects and to evaluate the diagnostic accuracy of these biomarkers for detecting oxidative stress in essential hypertension. METHODOLOGY: An analytical cross-sectional study was conducted at Civil (Dr. Ruth K.M. Pfau) Hospital Karachi from July 2020 to March 2021 after approval from the ethical committee. After informed consent, the serum oxidized low-density lipoprotein and glutathione levels were measured with ELISA's help in 40 normotensive and 40 early hypertensive participants. The results were analyzed by SPSS 21, keeping a significant p-value at <0.05. RESULTS: The median levels of Oxidized Low-Density Lipoprotein were higher in hypertensive than in normotensive (i.e. 31.47 ng/ml vs. 15.27 ng/ml). The median levels of glutathione were also raised in hypertensive compared with normotensive(i.e. 15.69 ng/ml vs. 4.46 ng/ml). The differences were significant (p-value <0.001). Both markers showed adequate diagnostic accuracy, sensitivity and specificity to detect oxidative stress in early hypertension. CONCLUSION: Oxidized Low-Density Lipoproteins are raised in early hypertension, endorsing the detrimental role of oxidative stress, while the levels of glutathione are increased to compensate for and combat increased oxidative stress in early hypertension. These biomarkers can be utilized clinically to discern the burden of oxidative stress in early hypertension.